Islamic Business Ethics in Live Selling Practices of Halal Culinary MSMEs in Padang City - Erizal Candra Efendi; Ahmad Wira; Rahma Yani Sania; Irwandi Jaswir (Faculty of Islamic Economics and Business, Madura Islamic State University, 2026)
Purpose – This study aims to analyze the implementation of Islamic business ethics in live selling practices among halal culinary MSMEs in Padang City and examine its influence on consumer trust and business sustainability. Methodology – This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving halal culinary MSME actors actively conducting live selling on digital platforms such as TikTok Live, Shopee Live, and Instagram Live. Data were analyzed using descriptive qualitative analysis based on the interactive model of Miles, Huberman, and Saldana. Findings – The findings reveal that live selling has become an important digital marketing strategy for halal culinary MSMEs in Padang City. Islamic business ethics principles such as honesty, transparency, politeness, sincerity, and halal assurance were consistently implemented during live selling activities. Ethical communication positively influenced consumer trust, customer loyalty, and business sustainability. However, MSMEs also faced several challenges, including intense digital market competition, limited digital ethical literacy, and communication difficulties during live streaming interactions. Implications – This study highlights the importance of strengthening digital ethical literacy and developing practical guidelines for sharia-based digital marketing among halal MSMEs. The findings may serve as references for policymakers, halal institutions, and educational organizations in designing ethical digital business training programs. Originality – This study contributes to Islamic business ethics literature by specifically examining the implementation of ethical values in real-time live selling practices among halal culinary MSMEs in Padang City, an area strongly influenced by Islamic cultural values